(3TQM NWHI ebOeI cJGH GdCKeGQs - (3jMji TQa GdOjf Hf TeS GdOjf Hf GdegOi dOjf Gddg CMeO Hf jMji Hf GdeQJVis
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , GdPi Od Ydi GdaQhY HGdCUhd , ceG Od Ydi GdCUhd HGdaQhY , hChUd HGdeSehY Edi GdeYbhd , ceG ChUd HGdeYbhd Edi GdeSehY EHJOC HGdHSedI s
(3BNQgG (B:s
(3HEYJHGQ bhI OGYi GdVQhQI EdjgG hhVhM GdEfYGe ef Gddg (B( (3hMOg (B) (3SHMGfg HgG hGddg SHMGfg hJYGdi CYde s
(3HgG HjGV dYdg ef GdfGSNs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdESdGejs